Towards Integrated Model of Big Data (BD), Business Intelligence (BI) and Knowledge Management (KM) - Chouk, Soud Kamoun; Berger, Hilary; Sie, Bing Hwie (Springer, 2017)
The emerging of Big Data (BD) in recent years as the latest development of Business Intelligence (BI) and Business Analytics (BA), representing new and unusual sources of data (e.g. social media, sensors), advanced technologies (e.g., Hadoop architectures, visualisation, predictive analytics), and new requirements of user skills (e.g., data scientists). This has a major impact on the fundamental of the traditional Business Intelligence (BI) and Knowledge Management (KM) processes.